Advancements in energy storage technologies: Implications for sustainable energy strategy and electricity supply towards sustainable development goals - Zhenkai Qin; Jing Ma; Mingfu Zhu; Talha Khan (Energy Strategy Reviews)
This research focuses on technological progress in energy storage for changing impacts concerning sustainable energy policies and electricity generation within the G-10 countries between 1996 and 2021. It discusses the improvements that energy storage technologies, including lithium-ion batteries, flow batteries, and hydrogen storage systems, bring to the power grid reliability, renewable energy integration, and carbon dioxide emission reduction. By developing a reciprocated relationship between energy storage technologies, renewable energy adoption, and technological advancement, the study offers a thorough analysis of the effects of each on the attainment of sustainable development goals 7 and 13. Thus, the application of the conclusions revealed that advanced energy storage technologies are essential for making energy systems more stable, reducing carbon emissions, and promoting the diversification of the economy in line with environmental objectives. Some policy guidelines include rising investments in energy storage innovations, development, supportive tax policies, and strengthening global cooperation. Therefore, this research highlights the importance of providing sufficient and relevant solutions for productive implementation to spread the international use of the energy storage system, which helps achieve other targets of net-zero development.